Limits on WIMP Dark Matter using Sapphire Cryogenic Detectors; Astroparticle Physics; Vol. 18, iss. 1 - Angloher G.; Bruckmayer M.; Bucci C.; Buhler M.; Cooper S.; Cozzini C.; Stefano P. Di; Feilitzsch F. von; Frank T.; Hauff D.; Jagemann T.; Jochum J.; et al. (2002, 2002)
Title screen